Netra Putpaka Kriya Kalpa: An Ayurvedic Perspective on Ocular Treatment - Meena, Renu; Vardhan, Prabhakar; Pamnani, Gulab Chand (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: The Ayurvedic Acharya, in the Samhita, highlighted the significance of the eye as a vital organ (Saravendranam Nayam Pradhanam). This study focuses on the Ayurvedic approach to ocular health, with an emphasis on the Kriyakalpa therapy for Netra Rogas, particularly the method of Putapaka. Methods: Acharya Sushruta advocated Putapaka as a key therapy for ocular conditions, integrating Tarpana and Putapaka Rasa in a unique manner. The method, described as considerably altered, is recommended for kapha dominant conditions but adaptable for vata and pitta imbalances. This article explores the Netra Putpaka Kriyakalpa, drawing insights from Ayurvedic texts for its detailed description. Results: Netra Putpaka emerges as a crucial therapeutic approach for eye diseases, emphasizing its efficacy in Ayurvedic ocular care. Despite being time-consuming and less commonly practiced by Shalakya professionals, its importance in treating various ocular conditions is underscored. Discussion: This article aims to bridge the gap between traditional Ayurvedic knowledge and contemporary scientific understanding. By sharing efficient methods for preparing Putapaka Rasa, the study emphasizes the relevance of Netra Putpaka in ocular treatment, providing valuable insights for the wider scientific community. Conclusion: Netra Putpaka Kriyakalpa stands out as a valuable Ayurvedic therapeutic modality for diverse eye conditions. This exploration contributes to the integration of traditional Ayurvedic practices into modern healthcare, promoting a holistic approach to ocular health.